IT Skills Assessment in Armenia - World Bank (Washington, DC, 2014)
The IT and high-technology sector is one of the fastest growing sectors in the Armenian economy. Since 2006, the sector, excluding Internet service providers, has grown with a CAGR of 22% reaching a total output of US$294 million in 2013. The number of companies operating in the sector is 380, the number of employees 8,000. About 13% of the companies operate in the high-technology domain, while the rest are IT companies. One of the driving factors of sector growth was its attractiveness for foreign companies to establish branches in Armenia. The prime competitiveness factor was the availability of relatively cheap and competitive human resources in Armenia. Currently, Armenia seems to be on the verge of losing this competitive advantage. Due to the growing number of IT companies in Armenia, demand for IT specialists will continue to increase. According to conservative estimates, if the market and productivity continue to grow with an average rate of 18% and 1% respectively, the absorption potential of additional IT specialists will grow at a rate of 17% annually and reach 15,000 by 2017. The sector is currently undergoing a major transformation: there is an increasing shift from the outsourcing model to the model of own product development and entrepreneurship in the sector. This model of growth requires a higher level of knowledge, new skills (such as sales and entrepreneurship skills), and entrepreneurial knowledge.